IMPLEMENTASI KEBIJAKAN LIGHT ON BAGI PENGENDARA SEPEDA MOTOR PADA SIANG HARI DI KOTA PONTIANAK - Februastuti E.01108061, Dwi (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article is intended to give insight on the Policy Implementation of Turning on The Main Light On for Motorists during Day Time in Pontianak City. In this article the problem focused on motorist who do not comply with his policy . Beside that there is no assertive action to the motorist that broke the law makes his policy useless. The result of analysis indicate that there is a gap between police authorities with the interpretation of motorist. The motorist thinks that light on policy doesn’t give any benefit even disserve them. Then the lack of decisive action or punishment are given rebuke comply with this policy made any motorists do not afraid if they violet this policy. If to given punishment is truly applied, the motorists will comply this policy. Keywords: The Light On Policy, Infringement Existence, In The Lack of Desicive Action.